Strategic Supply Chain Management in the Era of Industry Revolution 4.0 : A Study of Textile Industry in Bali - Juzer Juzer; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe purpose of this research is to understand every problem inside textile company in Bali island. In this 4.0 industrial revolution era, a textile company is forced to pay attention in all aspect in order to run company strategy. All issues like goods supply certainty, price, product variety, credit sales, regulation and digital marketing has been discussed in detail to make the leader understood about the difficulty and challenge inside the company. This research uses qualitative method and using SWOT analysis which explain in complete ways how strength, weakness, opportunity and threat in every issue that occurred in a textile company in Bali island. The writer used interview technic in detail way to collect data from all the informant in a textile industry chain link. The final purpose of this research is to improve textile industry in Bali island based on accurate facts and data.